THE ROLE OF THE FAMILY IN THE DEVELOPMENT OF A COMPLEX APPROACH TO THE PRONUNCIATION OF SOUNDS IN PRESCHOOL CHILDREN WITH HEARING IMPAIRMENT (Conferencea, 2022)
The role of the family in the development of pronunciation in preschool children with hearing impairments on the basis of a comprehensive approach, a system of planned work with children at home, an example of activities to be carried out at home.